2007
DOI: 10.1017/s1751731107683815
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changes in diet energy density on feed intake, milk yield and metabolic parameters in dairy cows in early lactation

Abstract: The purpose of this experiment was to investigate how early lactating cows adjust their metabolism and production to acute, but moderate changes in the energy density of the diet. Sixty dairy cows were randomly assigned to one of four treatments: two change-over groups (HNH and NHN) and two control groups (HHH and NNN), where H and N refer to a high and normal energy density in the total mixed ration (TMR), respectively. The experimental period covered the first 9 weeks post calving, which was split up in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
3
14
1
Order By: Relevance
“…It is noteworthy that the level of TAG pre-and post-calving was lower than has been reported elsewhere, whereas glycogen was similar (Andersen et al, 2002a;Nielsen et al, 2007). An explanation for the generally lower liver TAG content could be the relatively low losses of BCS post-calving in this study compared to the experiments mentioned earlier.…”
Section: Effect Of Diet On Post-calving Measuressupporting
confidence: 53%
“…It is noteworthy that the level of TAG pre-and post-calving was lower than has been reported elsewhere, whereas glycogen was similar (Andersen et al, 2002a;Nielsen et al, 2007). An explanation for the generally lower liver TAG content could be the relatively low losses of BCS post-calving in this study compared to the experiments mentioned earlier.…”
Section: Effect Of Diet On Post-calving Measuressupporting
confidence: 53%
“…The only effect on milk production during P2 was that of the severe (SS and MS cows) or moderate (SM and MM cows) treatment imposed during that period. The absence of a carryover effect on milk yield following feed restriction in early lactation has previously been described in short- (Nielsen et al, 2007) and long-term studies (Friggens et al, 1998;Delaby et al, 2009). Kennedy et al (2007), Roche (2007) and Kay et al (2011) reported a carryover effect on milk yield, but its duration was limited (,2 months) partly because the intensity of restriction at pasture remained moderate (PGSH of 3.1 to 5.2 cm).…”
Section: Effect Of Pgsh In Early Lactationmentioning
confidence: 75%
“…The absence of any delayed effect on milk yield due to feed management at the beginning of lactation, and the weak persistence of its influence on protein and fat content, has already been described in short-term (Nielsen et al, 2007) and longer-term trials (Coulon et al, 1996;Friggens et al, 1998). In certain trials (Kennedy et al, 2007;Roche, 2007), the authors describe a significant carryover effect on milk and fat yield, but its persistence is actually rather limited (1 to 2 months).…”
Section: Discussionmentioning
confidence: 87%